PENGARUH DERAJAT DEPRESI TERHADAP KADAR KOLESTEROL TOTAL SERUM AKIBAT ISOLATED SYSTOLIC HYPERTENSION DI KLINIK UTAMA KASEHAT WALAFIAT - Edi Cahyadi; Zurriyani Zurriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Background:Depression is a natural disorder of feelings that can be characterized by states such as melancholy, sadness, helplessness. In this disorder also sufferers can lose appetite, decreased appetite can also cause a decrease in cholesterol triglyceride levels. Cholesterol is a component of fat. Cholesterol in the body if it increases will cause lipid metabolism abnormalities characterized by increased or decreased lipid fraction, lipid fraction disorder causes cholesterol attached to the blood vessel wall and cause atherosclerosis resulting in narrowing of blood vessels resulting in increased blood pressure (hypertension). Hypertension is a state of increased blood pressure more than normal. Increased systolic blood pressure more than 140mmHg and diastolic pressure below 90mmHg. This study aims to determine the influence of depression degree on total serum cholesterol levels due to Isolated Systolic Hypertension at an advanced health facility in Aceh Besar in 2018. Method:This research is Observational Analytical by using cross sectional design. Sampling using accidental sampling technique and got sample 36 people consisting of 8 men and 28 women. Result:In this study found that cholesterol levels have a very small negative effect that is not significant to the classification of depression levels. This is because variable of cholesterol level has p-value value α (0,467 0,05). These results can be concluded that there is no influence of cholesterol levels on the classification of depression levels in the study subjects.Keywords: Depression, Cholesterol, Isolated Systolic Hypertension